(untitled) (Journal of Islamic Studies, 2023)
This study aims to determine the effect of the presentation of the program "Islam is Beautiful" on changes in the attitude of Trans TV viewers. The method in this study is quantitative descriptive with analytical case studies (case studies) and field research (field research). The sampling technique used purposive sampling, which was taken from the population in RT 013/RW 003 Pela Mampang Village, Mampang Prapatan District. As for the author’s research, it shows that Trans TV’s presentation of the program "Islam is Beautiful" has no effect on changing the behavior of the people of RT 013/RW 003 Pela Mampang Village. But more importantly, they can embrace the presentation of the program "Islam is Beautiful" and learn to gradually conduct good actions within the framework of amar ma’ruf nahi munkar, according to the level of comprehension of the Islamic teachings they follow.